Ekstrasi Minyak Biji Alpukat (Persea americana Mill) dengan Pelarut N-Hexane dalam Tangki Berpengaduk: Avocado Seed Oil (Persea americana Mill) Extraction with N-Hexane Solvent in a Stirred Tank - Ellena Hendrianti Permata Nagari; Hanah Sajidah; Dyah Suci Perwitasari (Program Studi Teknik Kimia, Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Avocado is a plant that can grow well in tropical climates such as Indonesia. Avocado fruit itself consists of 65% fruit flesh (mesocarp), 20% seeds (endocarp), and 15% skin (pericarp). Until now, the utilization of avocado seeds is still limited, so that it often becomes waste that has not been optimally utilized. In fact, avocado seeds have a starch content of 23%, which makes it an alternative source of starch that has the potential to be used in various industrial sectors, including food and pharmaceuticals. In addition, the high protein content in avocado seeds also makes it have good nutritional value. To utilize this potential, avocado seed oil can be extracted with the right method to produce maximum results. One method used in oil extraction is the mechanical extraction method, which involves pressure and the use of certain additional materials. In this study, the avocado seed oil extraction process was carried out with the help of n-hexane solvent and stirring techniques. Optimal results were obtained at a stirring speed of 500 RPM with an extraction duration of 110 minutes, resulting in an oil yield of 36.9%. Further research is needed to improve the effectiveness of oil extraction from avocado seeds so that the results obtained are more optimal. In the extraction method using n-hexane solvent and stirring technique, the best yield obtained was 19.8% at a stirring speed of 500 RPM for 110 minutes. The oil extracted from avocado seeds has a fat content of 39.77% of the total components that have been analyzed. Key words: Extraction, Avocado Seed, N-Hexane, Stirred Tank